PENGARUH ETIKA PERUSAHAAN DAN PEMBERDAYAAN KARYAWAN TERHADAP KOMITMEN ORGANISASI SERTA DAMPAKNYA PADA ORGANIZATIONAL CITIZENSHIP BEHAVIOR KARYAWAN PT TELKOM WILAYAH ACEH - Agus Friadi; Said Musnadi; Djuraidin Ismail (Jurnal Magister Manajemen, 2018)
The study aims to determine the effect of corporate ethics and employee empowerment on organizational commitment as well as its impact on the organizational citizenship behavior of PT Telkom regional Aceh. The study conducted of 218 employees of the corporate The data collected by questionnaire and then the data is analyzed by statistical means of structural equation model (SEM). The study found that  corporate ethics has a positive and significant effect on the organizational commitment and OCB. In contrast, the employee empowerment has no effect on organizational commitment, but it has a positive and significant effect on OCB. The organizational commitment mediates the effect of corporate ethics and employee empowerment on OCB of the employee of the corporation